2016
DOI: 10.9787/pbb.2016.4.4.462
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Useful Germplasm Based on the Variation Analysis of Growth and Seed Quality of Soybean Germplasms Grown at Two Different Latitudes

Abstract: We conducted this study to select useful germplasms for investigating the agricultural performances and content variations of proximate composition, fatty acid, and isoflavone of the soybean germplasms grown at two different latitudes, Suwon (37 o 16'N) and Yeoncheon (38 o 12'N), Republic of Korea. The days to flowering of the soybeans grown at Suwon was early by 1 day compared with that at Yeoncheon whereas the days to maturing of the soybeans were not different by latitudes. The Yeoncheon-cultivated soybeans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…We observed highly significant differences (P < 0.001) among the germplasm origins for all fatty acids (Table S3a). The significant variation of fatty acids among different germplasm origins was consistent with previous studies [20,21,28]. Grieshop and Fahey [31] reported that soybeans collected from various sources elucidated major differences in their nutritional composition of fatty acids.…”
Section: Effect Of Germplasm Origins On Variation In Seed Fatty Acid supporting
confidence: 91%
See 1 more Smart Citation
“…We observed highly significant differences (P < 0.001) among the germplasm origins for all fatty acids (Table S3a). The significant variation of fatty acids among different germplasm origins was consistent with previous studies [20,21,28]. Grieshop and Fahey [31] reported that soybeans collected from various sources elucidated major differences in their nutritional composition of fatty acids.…”
Section: Effect Of Germplasm Origins On Variation In Seed Fatty Acid supporting
confidence: 91%
“…Previous studies on seed fatty acid composition of several germplasm collections from different oil crops-such as sesame [23], Brassica species [24,25], and safflower [15,16,26]-have showed a wide variation for fatty acid composition. Likewise, many studies have been conducted on soybean seed fatty acid composition collected from various sources [20,21,[27][28][29][30]. These studies suggested that soybeans collected from various sources demonstrated key differences in their nutritional composition [31].…”
Section: Introductionmentioning
confidence: 99%
“…Soybean seed isoflavones contain 12 components which are divided into four groups, daidzein, genistein, glycitein (aglycones), daidzin, glycitin, genistin (glycosides), acetyldaidzin, acetylglycitin, and acetylgenistin (acetylglycosides), and malonyldaidzin, malonylglycitin, malonylgenistin (malonylglycosides) ( Kim et al., 2014 ; Azam et al., 2021 ). The malonyldaidzin, malonylglycitin, and malonylgenistin are the most abundant form of the isoflavones, while aglycones are present in very small amounts but have higher phytoestrogenic activity and more bioavailability in humans ( Nielsen and Williamson, 2007 ; Park et al., 2016 ; Azam et al., 2020 ). Improving soybean isoflavone content through conventional breeding and metabolic engineering is a complementary way for the biofortification of food crops to combat isoflavone deficiency ( De Steur et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxydaidzein represented a good correlation with genistin and daidzin derivatives; however, this compound showed a moderate correlation with glycitin derivatives. Among the isoflavones detected in soybean seeds, malonylglycosides are the most abundant, whereas their aglycones are in very low concentrations (Park et al ., 2016). The aglycones are particularly important due to their higher phytoestrogenic activity and better absorption in the human body (Nielsen & Williamson, 2007).…”
Section: Resultsmentioning
confidence: 99%